APLIKASI PUPUK PELENGKAP CAIR PADAKONSENTRASI BERBEDA TERHADAP BIBIT KELAPA SAWIT(ElaeisguineensisJacq.) YANG DITANAM PADA MEDIA GAMBUT YANG TERGENANG SECARA PERIODIK DENGANFREKWENSIPENYEMPROTAN BERBEDA - Tabrani, Gunawan; ', Ardinal; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to look at the interaction of PPC administration with different concentrations and different spraying frequency and get the best combination of the growth of oil palm seedlings were planted in peat media are flooded periodically. This research has been carried on in the greenhouse UPT Faculty of Agriculture, University of Riau, Pekanbaru, from November 2013 to February 2014. This study used a completely randomized factorial design consisting of two factors and three replications. The first factor was the concentration of PPC consists of 4 levels K0: no PPC, K1: 0.2%, K2: 0.4%, K3: 0.6% and the second factor the frequency of spraying PPC F1 consists of 3 levels: 1 times, F2: 2 times, F3: 3 times. Parameters measured were plant height increase, in the number of leaves, stem diameter, length of the primary root, root number, root volume, shoot root ratio. The mean separation of the tested by Duncan's multiple range test at 5%. The results showed the effect of interaction between the concentration and frequency of spraying PPC parameters contained in the stem base diameter, but not in the parameters as height of plants, increase the number of leaves, the primary root length, number of roots, root volume and shoot root ratio. A PPC concentration of 0.2% to 2 times, spraying showed the best growth at high accretion seed, in the number of leaves and root crown ratio, a PPC concentration of 0.6% with 3 times, spraying showed the best growth in root length, 1 time spraying on a number of roots, and 2 times spraying on the root volume. Keywords: oil palm, flooding, complementary liquid fertilizer and peat